Study of innovative activity of the distributive industries of the Russian Federation in the context of the world economy digitalization and globalization - Agaevich Ramazanov, Ibragim; Panasenko, Svetlana Viktorovna; Cheglov, Vyacheslav Petrovich; Krasil’nikova, Elena Anatol’evna; Fedorovich Nikishin, Alexander (Nexo Revista Científica, 2021)
The article presents the results of a study of innovative activity of companies in the trade sector. It is proved that Russian companies show low innovative activity in the commercial area. The authors conclude that the implementation of innovative activities in the context of the globalization of markets, the development of the digital economy, and the industrial revolution 4.0 is a necessary condition for the functioning of companies in the trade sector. Russian retail chains are entering a stage of crisis development and increased competition from global retail chains. Only those companies that are promptly aware of the need for innovative activity will be able to get out of the crisis.